Association mapping of plant sex and cross-compatibility related traits in white Guinea yam (Dioscorea rotundata Poir.) clones - Asfaw, A.; Mondo, J.; Agre, A.P.; Asiedu, R.; Akoroda, M.O. (Springer, 2022)
Background White Guinea yam (Dioscorea rotundata) is primarily a dioecious species with distinct male and female plants. Its breeding is constrained by sexual reproduction abnormalities, resulting in low success rates in cross-pollination. An accurate method for early detection of this plant’s sex and compatible fertile parents at the seedling stage would improve levels of cross-pollination success in breeding. We used the genome-wide association studies (GWAS) to dissect the molecular basis of plant sex and cross-compatibility-related traits in a panel of 112 parental clones used in D. rotundata crossing blocks from 2010 to 2020.